ANALISIS KEBUTUHAN DAN DESAIN BAHAN AJAR MATEMATIKA BERBASIS LITERASI NUMERASI PADA MATERI PECAHAN DI KELAS VII SMP - Asmaul Husnah; Usman Mulbar (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
Students’ low numeracy literacy skills in fractions are caused by teaching methods that remain focused on procedures and rote memorization without linking mathematical concepts to real-life contexts; therefore, innovative teaching materials are needed to support meaningful understanding. This study aims to analyze the needs and design numeracy-based mathematics teaching materials on fractions for seventh-grade junior high school students. This study uses a conceptual design approach with the Research and Development (R&D) method, limited to the needs analysis and product design stages. Data were obtained through a review of relevant literature on numeracy literacy, instructional materials, and fraction learning, and were analyzed using qualitative descriptive techniques. The results indicate that the instructional materials were designed as modules with a systematic structure, including concept maps, context-based content presentation, learning activities, student worksheets, numeracy literacy-based practice problems, reflections, and evaluations. The integration of real-life contexts into the modules enables students to understand fraction concepts in a more practical and meaningful way. Thus, these numeracy-based teaching materials have the potential to serve as an alternative in supporting more contextual and active mathematics learning, while promoting improvements in students’ numeracy skills.